The Feasibility Analysis of Mathematics Textbook Material based on Bell's Criteria - Mahendra Wisnu Wardana; Leetahannee Kadah (Hipotenusa : Journal of Mathematical Society, 2021)
The purpose of this study is to determine the feasibility of Mathematics textbook material for Grade VII 1st semester on 2017 Revised Edition based on Bell's criteria. So that if there is an error, it can be fixed. Then, this type of research is descriptive research. In the descriptive analysis, there is no need to find or explain its relationships and test hypotheses. The approach used is qualitative. Moreover, this study uses a qualitative approach because the data collected are described in sentences. This study will be obtained from two sources, namely the main source of the Mathematics Textbook Grade VII of 2013 curriculum and peer-discussion support sources. The method used in this research is the documentation method. The documentation data used in this research is the textbook itself. However, the data obtained by using the Analysis Instrument Result shows that the suitability of the mathematics textbook material of Grade VII with the material based on Bell's criteria for the numbers and algebra chapters includes a good category. Meanwhile, the sets and equations and linear inequalities of one variable chapter belong to be an excellent category. The average suitability of the mathematics material from each chapter in the textbook toward Bell's criteria is 83.75% and is supported by the validity data results through forms and peer discussions. As a result, the feasibility of the mathematics textbook material for grade VII of the 2017 revised edition based on Bell's criteria is very good.